The relationship between technostress creators and job satisfaction among support staff at Sarawak Energy Berhad/ Nurhafiza Shahira Zulkernain - Zulkernain, Nurhafiza Shahira (2017)
Due to the changes in technology, it has affected the users. Technology is designed to help the user, unfortunately, it has caused problems and stress to the users. Technostress happened due to the rapid changes in computer technologies and it may increase user’s job dissatisfaction. Thus, this study aimed to investigate the relationship between technostress and job satisfaction among administrative staff at Sarawak Energy Berhad. 120 questionnaires were distributed however, only 92 questionnaires (N=92) were ascertained as useable for analyses. The results from questionnaire collected from 92 respondents showed, there was negative correlation coefficient between technostress and job satisfaction. There were negative, low and significant relationship between Techno- Overload on Job Satisfaction (r= -.215* , p< 0.05). Besides, there were negative, medium and significant relationship between Techno-Invasion and Job Satisfaction (r= -.321**, p>0.01). While, the relationship between Techno-Uncertainty and Job Satisfaction (r= -.297**, p>0.01) were negative, low and significant. The negative correlation coefficient explains that increase in technostress led to decreases in job satisfaction. Since the results explained increment in technostress would led to job dissatisfaction, the organisation is suggested to find productive ways to avoid their employee’s technostress and job dissatisfaction in the organisation.